Overriding Mandatory Rules in EU Private International Law - Dominika Moravcová (Bratislava Law Review)
As a result of the increasing incidence of private law relationships with a foreign element, courts hearing cases are frequently obliged to apply foreign law. The interference of foreign law is liable to produce effects that may conflict with the public interest of the lex fori. Precisely for this reason, we consider it essential to be aware of the available protective mechanisms through which the court can protect the public interest, not only of the lex fori, but even, under certain circumstances, of the public interest of the foreign legal order. The present article deals with the mechanism of overriding mandatory provisions in private international law in order to identify the requirements for the activation of the selected mechanism in the Slovak courts' application practice. Given that this mechanism is not covered by the Slovak Act on International Private and Procedural Law, the article deals mainly with the rules enshrined in the Rome I Regulation. The first part of the present article deals with the definition of overriding mandatory provisions, the application in private international law, and the historical perspectives in the light of the so-called Rome Convention. Subsequently, the article focuses on the classification of overriding mandatory provisions and their impact within the limits relevant to Slovak courts.